2019
DOI: 10.3168/jds.2019-16630
|View full text |Cite
|
Sign up to set email alerts
|

Meloxicam affects the inflammatory responses of bovine mammary epithelial cells

Abstract: Nonsteroidal anti-inflammatory drugs are used as supportive therapy with antimicrobial treatments for mastitis in cows to alleviate pain of the inflamed mammary gland. They act mainly by inhibition of cyclooxygenases. Meloxicam (MEL) is a drug designed for cyclooxygenase-2 selectivity, which is upregulated upon inflammation, acting as a key enzyme for the conversion of arachidonic acid to prostaglandins. Although some studies in dairy cows showed positive results in recovery from mastitis when MEL was added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
(40 reference statements)
5
23
1
Order By: Relevance
“…Our data support the local role of oral meloxicam in the mammary gland, which likely decreases local inflammation, thus favoring both immunoglobulin recruitment from plasma and local production of IgA in plasma cells (1). Indeed, in vitro studies developed in cattle have shown the anti-inflammatory effect of meloxicam in mammary epithelial cells (25). Furthermore, mastitis in cows has been associated with reduced pre-weaning immunity, growth, and health of the offspring (26,27), so the anti-inflammatory effect elicited by meloxicam treatment is presumed to have the opposite effect.…”
Section: Transfer Of Passive and Active Immunitysupporting
confidence: 79%
“…Our data support the local role of oral meloxicam in the mammary gland, which likely decreases local inflammation, thus favoring both immunoglobulin recruitment from plasma and local production of IgA in plasma cells (1). Indeed, in vitro studies developed in cattle have shown the anti-inflammatory effect of meloxicam in mammary epithelial cells (25). Furthermore, mastitis in cows has been associated with reduced pre-weaning immunity, growth, and health of the offspring (26,27), so the anti-inflammatory effect elicited by meloxicam treatment is presumed to have the opposite effect.…”
Section: Transfer Of Passive and Active Immunitysupporting
confidence: 79%
“…The in vitro pro-apoptotic effect of lornoxicam on camel leukocytes at concentrations that can be easily reached in plasma after the administration of lornoxicam in vivo indicates a role for lornoxicaminduced cell death in the reduced leukocyte numbers in lornoxicam-injected camels. A similar detrimental effect on cell viability was reported in bovine mammary epithelial cells treated with meloxicam [31]. Cell apoptosis is mainly regulated by caspases, a family of cysteine proteases, including caspase-2, -8, -9, -10, -11, and -12.…”
Section: Discussionsupporting
confidence: 71%
“…The construction of mastitis model of cows was frequently based on 1 μg/mL LPS stimulation for BMECs in vitro in many studies [ 33 , 34 , 35 , 36 , 37 ]. There were some studies which reported that a lower concentration of LPS, such as 0.1 [ 38 , 39 ], 0.2 [ 40 , 41 ], 0.5 [ 42 ] μg/mL and so on, could also induce inflammatory responses of BMECs. In the present study, 0.01 μg/mL LPS only significantly promoted the gene expression of IL-6 and IL-8 .…”
Section: Discussionmentioning
confidence: 99%